2009
DOI: 10.1038/nature08062
|View full text |Cite
|
Sign up to set email alerts
|

Down's syndrome suppression of tumour growth and the role of the calcineurin inhibitor DSCR1

Abstract: The incidence of many cancer types is significantly reduced in individuals with Down syndrome1–4 and it is proposed that this broad cancer protection is conferred by the elevated expression of one or more of the 231 supernumerary genes on the extra copy of chromosome 21. One such gene is the Down syndrome candidate region-1 (Dscr1, RCAN1), which encodes a protein that suppresses vascular endothelial growth factor (VEGF)-mediated angiogenic signalling via the calcineurin pathway5–10. Here we show that DSCR1 is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
299
0
7

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 344 publications
(340 citation statements)
references
References 29 publications
20
299
0
7
Order By: Relevance
“…They suggested that these lesions should be considered to be ''telangiectatic HCA'' (THCA). 4 In 2005, Bioulac-Sage et al reached the same conclusion using different molecular techniques 5 and included in 2007 the so-called ''TFNH'' in the subgroup of inflammatory HCAs. 6 Finally, in 2009, the basis of the inflammatory phenotype was elucidated by the identification of the mutations activating gp130 in most of the inflammatory HCAs exhibiting sinusoidal dilation or not.…”
Section: An Indicator For Evaluating the Risk Of Cancerous Transformamentioning
confidence: 90%
See 2 more Smart Citations
“…They suggested that these lesions should be considered to be ''telangiectatic HCA'' (THCA). 4 In 2005, Bioulac-Sage et al reached the same conclusion using different molecular techniques 5 and included in 2007 the so-called ''TFNH'' in the subgroup of inflammatory HCAs. 6 Finally, in 2009, the basis of the inflammatory phenotype was elucidated by the identification of the mutations activating gp130 in most of the inflammatory HCAs exhibiting sinusoidal dilation or not.…”
Section: An Indicator For Evaluating the Risk Of Cancerous Transformamentioning
confidence: 90%
“…2,3 Furthermore, microvessel density (MVD) has been widely used as a marker of tumor angiogenesis, and has been associated with outcome of cancer therapy. 4 Therefore, we investigated MVD within teratomas in SCID mice into which human iPSCs established by Oct3/4, Sox2, and Klf4, according to the methods of Nakagawa et al, 3 were transplanted.…”
Section: An Indicator For Evaluating the Risk Of Cancerous Transformamentioning
confidence: 99%
See 1 more Smart Citation
“…S1 and S2). It is important to note that the levels of intersectin1, synaptojanin1, and DSCR1 proteins have been shown to be elevated at a comparable amount in either human DS patient tissues or Ts65Dn mouse, a commonly used mouse DS model (ranging from Ϸ1.4-to 1.8-fold increases have been reported) (6,(39)(40)(41). Thus, our transgenic flies provide us a model system to investigate whether a dominant key gene or a subset of genes interact to affect phenotypes seen in DS.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, endostatin and related DS genes have been shown to downregulate VEGF signaling through inhibition of calciumcalcineurin NF-AT (nuclear factor of activated T cells) activities, which attenuate endothelial proliferation and angiogenesis. [137][138][139][140][141][142][143] Whereas these factors may be beneficial for protecting against tumor angiogenesis, we hypothe- . Three-dimensional reconstruction of distal lung tissue, illustrating intrapulmonary arteriovenous communications ("shunt vessels") in infant with severe bronchopulmonary dysplasia (BPD).…”
Section: Pvd In Bpdmentioning
confidence: 99%